PENERAPAN MODEL PBL BERBANTUAN MEDIA PAPAN BAHAN BAKU DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD - Sholikha, Dea Kamelia; Candra Dewi; Amalya Trisuci Dewanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to improve the critical thinking skills of class V students at SDN 03 Madiun Lor by implementing the Problem Based Learning (PBL) model using raw material boards. This classroom action research (PTK) involved 25 students. Data analysis used quantitative data. Quantitative data is used to measure students' critical thinking abilities by using tests in the form of essay questions that are adjusted to indicators of critical thinking abilities. In the first cycle, the average critical thinking ability test score was 70.88 with a classical completion level of 48%. In the second cycle, the average score increased to 84.32 with a classical completion level of 88%. This shows that the application of the PBL model using raw material board media is effective in improving students' critical thinking skills.